Health problems of foreign workers - microbiological investigations - Ngeow, Yun Fong; Ng, Kee Peng; Puthucheary, Savithri Devi; Lam, Sai Kit (Faculty of Medicine, University of Malaya, 2002)
Foreign workers in Malaysia are screened for certain infectious diseases prior to their entry to the country but some escape medical screening and others acquire infection during their stay in the country. The Faculty of Medicine, University of Malaya was commissioned to study the impact of foreign labour on the local health system and, as part of the investigations, 584 foreign workers attending local outpatient clinics were examined for serological evidence of syphilis, HIV infection, viral hepatitis B, C and E, as well as for enteric infections by Salmonella, Shigella and Vibrio cholerae. The results showed that apart from viral hepatitis E, the prevalence rates of the infections looked for were not notably higher than those for the general Malaysian population. The seroprevalence rates obtained were 2.6% for syphilis, 0.2% HIV infection, 3.8% viral hepatitis B, 1.0% viral hepatitis C, 14.4% viral hepatitis E. The detection of HEV lgM in 7.7% of the workers screened indicates that these infections could have been acquired during their stay in Malaysia.